Factors influencing depressive symptoms in Chinese female breast cancer patients: a meta-analysis - Zhang, Qingyuan; Wu, Gen; Chen, Jianfei; Fang, Kui; Liu, Qianqian; Zhang, Pan; Zhu, Hongzhen; Zhang, Chunhua (Frontiers in Psychology, 2024)
Objective: To systematically evaluate and explore the factors influencing depressive symptoms in female breast cancer patients in China through Meta-analysis.: Relevant data were retrieved from cross-sectional studies or cohort studies on depressive symptoms of Chinese breast cancer within the following databases: PubMed, Embase , Cohrane Library, Web of 105 Science, Database of Medical Literature (CBM), Wan Fang Data, CNKI, and VIP databases. The literature screening, data extraction and literature quality evaluation were performed by two researchers by carefully reading the title, abstract and full text, and Meta-analysis was performed using Stata 1.5 software after extracting relevant data.Result：Fourteen papers were finally included, with a cumulative total of 3071 people surveyed, and a total of 1298 breast cancer patients were detected with depression, with a detection rate of depressive symptoms of 42.26%; Meta analysis showed that age less than 40 years old, unmarried, less than undergraduate education, monthly income less than 5000 yuan, advanced breast cancer, radical breast cancer surgery, family history, living in rural areas, underlying disease stage and chemotherapy were associated with an increased incidence of depression in breast cancer patients.